O wspominaniu świętych podczas proskomidii. - Charkiewicz, Jarosław (Elpis, 2014)
There is a very strong presence of the saints in the Orthodox Divine Liturgy, One of two main places of their presence (besides the anaphora) is proskomidia. This part of the Liturgy had been absent in this main Christian service for first centuries. The first signs of appearance of the proskomidia in the Liturgy had a place in VIII–IX centuries, but in XII–XIII centuries only it became a separate part of this service. It was finally formed in XVI-XVII. The article gives a wide vies on the historical development of the proskomidia and the place of the saints in it. It treats also on the development and meaning of the different number of prosphoras used in the Liturgy, as well as the problem of commemoration of the angels and the Holy Cross in proskomidia. The author describes also the character of the commemoration of the saints in proskomidia and the main differences that are present on Greek and Slavonic proskomidias. He also explains the nuances of different types of the sanctity of the saints that are present in proskomidia the Orthodox Church.